The influence of spin-orbit coupling on the band gap of Heusler alloys - P. Mavropoulos; Galanakis, I.; Popescu, V; P.H. Dederichs (JOURNAL OF PHYSICS-CONDENSED MATTER, 2004)
The band gap of half-metallic ferromagnets can be affected by the spin-orbit coupling, which introduces there a small, but non-vanishing, density of states. We study this effect in the case of Heusler alloys. We find that, as a rule, the spin polarization in the middle of the gap decreases for compounds of heavier elements.